2020
DOI: 10.36997/ijuev2020.64.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Funding of Micro Scale Enterprises: Is Cooperative Financing Helpful?

Abstract: The study investigates the influence of cooperative financing on the performance and survival of micro scale businesses, in Ogun State, Nigeria. A survey research design was adopted to generate crosssectional data, using a structured questionnaire as the research instrument. From a population of 1,165,848 a sample size of 384 was obtained using the Raosoft sapling size formulae. Regression analysis was used to analyze the data. The findings revealed that cooperatively sourced finance has a positive and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…As the borrower increased loans from other sources the more the rate of defaulting the AFC loan. This finding conformed to observation by Oluwasanya [64] who reported logit results that showed that multiple borrowing, was statistically significant and had a marginal of 0.1092 meaning that with increase in the number of loan borrowings, default rate also increased.…”
Section: Description Of the Econometric Models On The Effect Of Borro...supporting
confidence: 91%
“…As the borrower increased loans from other sources the more the rate of defaulting the AFC loan. This finding conformed to observation by Oluwasanya [64] who reported logit results that showed that multiple borrowing, was statistically significant and had a marginal of 0.1092 meaning that with increase in the number of loan borrowings, default rate also increased.…”
Section: Description Of the Econometric Models On The Effect Of Borro...supporting
confidence: 91%
“…In emerging economies, SMEs have generated about 45% of total employment (OECD, 2017). Reinforcing the above statement, Ogunmuyiwa and Okunleye (2019) corroborated that small enterprises contributed about 70% of industrial employment and 50% of manufacturing output in Nigeria. This justifies the necessity for the exploration of SMEs in employment generation in particular and the development of the economy as a whole.…”
Section: Introductionmentioning
confidence: 68%
“…The number of micro-scale businesses in Batu City is greater than small-scale businesses, around 85% of businesses are small-scale. Micro-scale businesses are more dominant [48] due to lower capital, limited human resources, local economic environment, ease of licensing, and limited education and skills [49][50][51]. Therefore, the micro-scale business sector can support the global economy [52][53].…”
Section: Potato Chips Industry Profilementioning
confidence: 99%